COVID-19 infection and thyroid function (Eurasian Medical Research Periodical, 2022)
The novel coronavirus, known as severe acute respiratory syndrome coronavirus-2 (SARS-COV-2), is the cause of the global coronavirus 19 (COVID-19) pandemic that began in late 2019. COVID-19 infection can range from very mild to asymptomatic leading to critical illness and death. Along with several organ systems that can be affected by COVID19 is the thyroid gland. In some patients, COVID-19 infection can trigger a hypersensitive immune response and widespread inflammation, known as a “cytokine storm.” Since the most common causes of thyroid problems are antibodies attacking the thyroid (autoimmune thyroid disease), this activation of the immune system can also cause inflammation and thyroid dysfunction